Effect of self‐administered stretching on NIRS‐measured oxygenation dynamics. (17th October 2014) - Kruse, Nicholas T.; Scheuermann, Barry W.
Summary: This study determined human skeletal muscle oxygenation dynamics during and after a single bout of self‐administered stretching (SAS) of the plantar flexors. Nine healthy recreationally fit men ( n  = 7; age = 25·7 years) and women ( n  = 2; age = 23·5 years) performed two protocols: (i) one bout of SAS for 4 min and (ii) one bout of moderate intensity cycling for 4 min. We used near infrared spectroscopy to measure changes in muscle deoxygenated haemoglobin–myoglobin ([HHb]) and blood volume ([Hbtot ]) of gastrocnemius medialis muscle before, during and after stretching. The SAS caused an increase ( P <0·05) in [HHb] during stretching between 60 and 240 s relative to baseline, but not at 30 s. No significant difference was found for [Hbtot ] at any time interval during SAS. Furthermore, the increase in local blood flow (suggested by [Hbtot ] changes) was found to be significantly increased relative to baseline at 1, 5 and 10 min after SAS, thus providing novel evidence for a poststretch hyperaemia. No significant interaction for [HHb] was found between stretching and cycling conditions, suggesting that the metabolic disturbance during stretching closely resembles moderate intensity exercise. These findings suggest that a single self‐administered stretch for 60 s can produce a substantial microcirculatory event and that blood flow may be enhanced for up to 10 min after stretching.